Bifunctional copper ion/melittin incorporated hydrogel with antimicrobial and antioxidant capabilities for infected skin wound healing - Jun Yao; Xiao Li; Minjie Lin; Zhuoqi Han; Xiaonan Wang; Jingjing Guo; Bing Wu; Jiajie Xia (Materials & Design)
Skin infections present a major clinical challenge, as bacterial invasion and inflammation can complicate wound healing. Therefore, bacterial infections must be treated while the accompanying inflammation and oxidative stress are regulated. Owing to the ongoing global increase in bacterial resistance, in this study, hydrogel co-loaded with bio-antimicrobial peptides and copper ions is designed, which exhibits antimicrobial, anti-inflammatory, and antioxidant properties. the proposed, sodium alginate@copper hydrogel (SA@Cu) is formed through the cross-linking of sodium alginate and Cu2+. Melittin (MEL) is then loaded to prepare a SA@Cu-MEL hydrogel. We optimised the sodium alginate and Cu2+ and MEL concentrations in SA@Cu-MEL hydrogels using Response Surface Methodology method. The proposed SA@Cu-MEL hydrogel exhibits significant antibacterial activity against Staphylococcus aureus and Escherichia coli, as well as good mechanical properties, self-healing ability, and MEL slow-release behaviour. Additionally, the SA@Cu-MEL hydrogel reduces inflammatory responses, promotes macrophage polarisation to the anti-inflammatory M2 type, and facilitates NIH cell proliferation and migration. In rat models, SA@Cu-MEL significantly accelerated wound healing, enhancing angiogenesis and collagen deposition. The optimised hydrogel not only reduces MEL toxicity but also amplifies its antibacterial and anti-inflammatory effects. Therefore, the proposed hydrogel has promising potential application in the treatment of infected skin wounds.